Runoff Regimes along Altitudinal Transects and Their Potential for Model Building - A Comparison Between Peru and Austria - Cárdenas Gaudry, María Magdalena (2015)
Descargue la tesis en el repositorio institucional de la Technische Universität Wien: http://hdl.handle.net/20.500.12708/2829